Music and Corporeal Mimesis: creative frictions for the dramaturgy of the musician-actuator - Souza, Eduardo Conegundes (Revista Brasileira de Estudos da Presença, 2021)
Built as a cartographic report, this article aims to give insight to the practical and conceptual procedures carried out during the research process that culminated in the scenic and musical creation of the show Uji – O Bom da Roda. Based on the cartographic method, we focus on encounters and contaminations produced between the theatrical universe and the roda de samba (samba circle) in its multiple expressive dimensions. Within a territory of creative frictions, Corporeal Mimesis presented itself as a fundamental element of articulation between music, body, scene and dramaturgy.